In-depth characterization of Lactobacillus delbrueckii subsp. lactis 313 for growth and cell-envelope-associated proteinase production - Agyei, D.; Danquah, Michael (ELSEVIER, 2012)
The effect of process conditions on the growth and production of cell-envelope-associated proteinase (PrtL) by Lactobacillus delbrueckii subsp. lactis ATCC ® 7830™ (LDL 313) was studied. Cell growth was profuse under the temperature conditions of 37°C, 40°C and 45°C, with cell growth rates, µ max increasing with temperatures. Initial culture pH of 6 displayed the highest PrtL yield of 2.33U. For each growth temperature the cell growth rates under anaerobic conditions were markedly higher than microaerophilic conditions, attributable to efficient sugar utilization under anaerobic fermentation. Overall, the proteolytic activities of cell-bound PrtL (bPrtL) were found to be higher than that of released PrtL (rPrtL). Higher rPrtL activities were displayed by anaerobic cultures over the entire fermentation period whereas the converse was true for bPrtL with microaerophilic cultures in the mid-late exponential phase displaying higher bPrtL activities than anaerobic cultures. Further, the proteinases had caseinolytic specificity for ß-casein and k-casein placing them in the cell-envelope-associated proteinases (CEPs) class I (CEP I) of the lactococcal CEPs grouping. This study provides insights into conditions for profuse growth and proteinase production by LDL 313 for subsequent technological applications in fermented foods, the dairy industry and bioactive peptide production.